Syntactic Peculiarities in Conversational Discourse of American Undergraduate Students: Sociolinguistic perspective - Velyan, Karen (Armenian Folia Anglistika, 2008)
It is common knowledge that public dialects are conditioned by the social position, education, as well as age peculiarities of the speaker. The latter plays an important role in the choice of the linguistic units since speakers, dependent on their age, tend to use different syntactic structures in their conversational discourse. Moreover, differences in syntax can be observed in the conversation of female and male representatives of the society.The given article examines the syntactic peculiarities in conversational discourse of American undergraduate students aged 20-21. The analysis has been conducted by the author of the article based on the recordings of the speech of American students in the USA. The article namely specifies the types of syntactic structures, complex sentences that are more frequent among US students.